Relationship Between Perceived Stress and Quality of Life of Nurses Working in COVID-19 Wards - Tahereh Heidari; Azar Jafari-Koulaee; Hamideh Azimi Lolaty; Majid Khorram; Soraya Rezaei; Abolfazl Hosseinnataj (ACHSM, 2023)
Background: Stressors during the COVID-19 pandemic, led to lack of concentration and lack of energy to achieve career goals, fatigue, poor performance, burnout and reduced quality of life of people, especially nurses. Methods: This descriptive-analytical study was done with the aim of determining the relationship between perceived stress and quality of life of nurses working in the care wards of patients with COVID-19 in hospitals affiliated to Mazandaran University of Medical Sciences (Mazandaran, Iran) during 2020-2021. Inclusion criteria included willingness to participate in the study, having at least a bachelor's degree in nursing and working in the care wards of patients COVID-19. Data collection tools included demographic information questionnaire, Cohen Perceived Stress Questionnaire and WHO Quality of Life Questionnaire. Frequency, percentage, Mean and standard deviation indices were used to describe the variables. Also, Mann-Whitney, Kruskal-Wallis and Spearman correlation coefficients were used to ass the relationship between variables. Results: The Mean (SD) age of participants was 33.48 (6.64) years. Most were female (%73.3). The total scores of quality of life and perceived stress variables of nurses were 47.63±24.31 and 27.62±4.61, respectively. Nurses' scores of quality of life domains included Physical Health, Psychological, Social Relationships and environmental domain were 46.52±12.69, 46.57±12.70, 46.39±19.45 and 50.52±10.52, respectively. Nurses' quality of life had a direct significant relationship with the variables of sleep quality and job satisfaction (P<0.001). Perceived stress score also had a significant inverse relationship with physical and social dimensions and total quality of life score (P<0.001). Conclusions: Based on the results of this study and the negative effects of nurses' perceived stress on their quality of life, it is necessary to pay serious attention to nurses' concerns. It is recommended to Be considered appropriate interventions to reduce perceived stress and improve the quality of life in nurses who care for patients with Covid-19.